Denunciator: type of applicant or individual participant in criminal proceedings - Oheruk I.; Zahursky O. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose: The purpose of this work is to analyze the current legislation concerning the denunciator as a participant in criminal proceedings and to determine the extent to which their procedural status aligns with the provisions of Ukraine’s criminal procedural and anti-corruption legislation.